THE COST-QUALITY PARADOX IN HEALTH CARE REFORM: AN IN-DEPTH CRITICAL REVIEW - Hussain Hadi Ali Alaldbey, Mohsen Mohammed YahyaAl Askar, Mahdi Hasan A Al Murdef, Ahmed Nasser Mane Alshahi, Hassan Masud Mane ALsenan (Chelonian Research Foundation, 2023)
The enactment of health care reform initiatives has been pivotal in shaping the landscape of health care systems worldwide, aiming to enhance accessibility, improve quality, and control costs. However, these reforms often bring forth a paradoxical situation where the interplay between cost containment and quality enhancement becomes a complex challenge. This article delves into the "Cost-Quality Paradox" in health care reform, critically reviewing existing literature and case studies to unpack the nuanced impacts of various reform measures. Through a methodical examination, it highlights instances where reforms intended to reduce costs inadvertently affect service quality, and conversely, where quality initiatives elevate costs, creating a balancing act for policymakers. The review further explores innovative strategies that have been successful in mitigating this paradox, offering insights into integrated approaches that simultaneously address cost and quality. By synthesizing current findings and drawing on diverse reform examples, this article provides a comprehensive overview of the challenges and opportunities presented by health care reform in the context of the cost-quality paradigm. Keywords: Health Care Reform, Cost-Quality Paradox, Service Quality, Cost Containment, Policy Analysis, Integrated Health Care Strategies, Health Care Systems, Health Policy, Quality Improvement, Cost Efficiency.